QUALIDADE ACÚSTICA EM SALAS DE AULA: CONTRIBUIÇÕES À GESTÃO DA MANUTENÇÃO - Souza, Robert Silva de (2021)
the environments in which the human being develops his activities can affect both his physical and his emotional state. Lighting, noise, temperature, ventilation, odors, among other factors, need attention when preparing building projects. However, it was